59Co NMR, a tool for the study of the structure, reactivity and supramolecular chemistry of Co(III) complexes derived from a series of N-alkyl-N-alkyl(aryl)-N’-acyl(aroyl)thioureas - Barnard, Ilse (Stellenbosch : Stellenbosch University, 2020, 2020)
Thesis (PhD)--Stellenbosch University, 2020.